Formation mechanism of dense anti-oxidation layer in Al-Si-MgO composites sintered in air condition. Issue 4 (March 2018) - Sun, Yang; Li, Yong; Li, Hongyu; Yan, Mingwei; Tong, Shanghao; Sun, Jialin
Abstract: An Al-Si-MgO composite was prepared at 1450 °C for 2 h in air using aluminium powder, silicon powder and magnesia powder as raw materials. The calcined composite was characterized and analyzed by XRD, SEM and EDS. The results show that after being calcined, Al and Si in the composite reacted to form MgAl2 O4 and Mg2 SiO4 respectively, rather than the low melting point phase located within the MgO-Al2 O3 -SiO2 system. At high temperature, Al2 O (g) and Mg (g) can be formed and spread along the pores in the specimen owing to the inhomogeneous gas concentration, and then oxidized by O2 (g). Owing to the deposition of Al2 O3 and MgO and the volume expansion caused by Si transformation into SiO2, a dense layer containing MgO, MgAl2 O4 and Mg2 SiO4 finally forms close to the surface of Al-Si-MgO composite. The formation of the dense layer improves the antioxidant properties of the composite, forms a plate-like AlN polytype and leads to the retention of the unreacted Si in the centre of Al-Si-MgO composite. In addition, the formation mechanism for the dense layer in the Al-Si-MgO composite was also established in this work.